2017
DOI: 10.1111/1471-0528.14900
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative effects of mifepristone for dilation and evacuation after 19 weeks of gestation: a randomised controlled trial

Abstract: Mifepristone and misoprostol for cervical preparation prior to D&E has potential to reduce barriers to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…We found that procedures performed at 15–18 weeks' gestation after cervical preparation with mifepristone and misoprostol did not take significantly longer to complete than those performed after overnight preparation with osmotic dilators. This is consistent with findings in a study of surgical abortion after 19 weeks, in which mifepristone in combination with misoprostol had similar operative times compared with preparation with osmotic dilators 16…”
Section: Discussionsupporting
confidence: 90%
“…We found that procedures performed at 15–18 weeks' gestation after cervical preparation with mifepristone and misoprostol did not take significantly longer to complete than those performed after overnight preparation with osmotic dilators. This is consistent with findings in a study of surgical abortion after 19 weeks, in which mifepristone in combination with misoprostol had similar operative times compared with preparation with osmotic dilators 16…”
Section: Discussionsupporting
confidence: 90%
“…Limitations of the study include the few available studies, both of which were challenged with achieving recruitment goals. It is possible that there have been developments in service delivery of second-trimester medical and surgical abortion or in clinical protocols, including management of cervical dilation and pain, that might impact on the acceptability of either method now or in the future 21 22…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive mifepristone and misoprostol trended towards a shorter procedure time compared to adjunctive misoprostol alone in the most advanced gestational age cohort, but was not statistically significant (10 vs 13 min, p = 0.42). More importantly, elimination of osmotic dilators led to more cervical lacerations, demonstrating their continued importance for safe cervical dilation in late second trimester D&E procedures [24].…”
Section: Methodsmentioning
confidence: 99%